The role of vitamin D in cardiovascular disease and COVID-19 - Driggin, Elissa; Madhavan, Mahesh V.; Gupta, Aakriti (Reviews in endocrine & metabolic disorders, 2022)
Patients with pre-existing cardiovascular disease (CVD) are at high risk for adverse outcomes with coronavirus disease 2019 (COVID-19). Further, COVID-19 infection is associated with numerous cardiovascular (CV) complications including arrhythmia, myocardial injury, cardiomyopathy, and thrombotic events. Increased susceptibility to COVID-19 and CV complications related to COVID-19 may be in part related to immune dysregulation and inflammation associated with CV disease which is exacerbated with viral infection. Vitamin D plays a major role in immune function and exerts anti-inflammatory effects, which may prove important in the context of CVD and COVID-19. To date, studies have shown minimal benefit for vitamin D supplementation in patients with COVID-19, though there are no studies specific to patients with CVD and related complications. Further, given that vitamin D has important protective effects on the CV system, including augmentation of myocardial contractility and anti-thrombotic effects, it is unknown if supplementation with vitamin D can mitigate CVD complications associated with COVID-19.